Changes in patterns of neural activity underlie a time‐dependent transformation of memory in rats and humans. Issue 10 (21st November 2018) - Sekeres, Melanie J.; Winocur, Gordon; Moscovitch, Morris; Anderson, John A. E.; Pishdadian, Sara; Martin Wojtowicz, J.; St‐Laurent, Marie; McAndrews, Mary Pat; Grady, Cheryl L.
Abstract: The dynamic process of memory consolidation involves a reorganization of brain regions that support a memory trace over time, but exactly how the network reorganizes as the memory changes remains unclear. We present novel converging evidence from studies of animals (rats) and humans for the time‐dependent reorganization and transformation of different types of memory as measured both by behavior and brain activation. We find that context‐specific memories in rats, and naturalistic episodic memories in humans, lose precision over time and activity in the hippocampus decreases. If, however, the retrieved memories retain contextual or perceptual detail, the hippocampus is engaged similarly at recent and remote timepoints. As the interval between the timepoint increases, the medial prefrontal cortex is engaged increasingly during memory retrieval, regardless of the context or the amount of retrieved detail. Moreover, these hippocampal‐frontal shifts are accompanied by corresponding changes in a network of cortical structures mediating perceptually‐detailed as well as less precise, schematic memories. These findings provide cross‐species evidence for the crucial interplay between hippocampus and neocortex that reflects changes in memory representation over time and underlies systems consolidation.